Avaliação da composição fitoquímica, citotoxicidade e efeito antimicobacteriano de extratos de frutas vermelhas e silvestres - Vincensi, Thiana Maccangnan (2024)
The recent increase in tuberculosis cases has once again caused concern for the World Health Organization, as has the antimicrobial resistance that Mycobacterium tuberculosis (MTB) has acquired. It is necessary to seek new treatments and medicinal plants are a source for new pharmaceutical compounds. Red and wild fruits are rich in phenolic compounds, which are substances with antimicrobial activity and have antioxidant capacity. The objective of the study was to analyze the extracts of Cranberry, Jabuticaba, Blueberry and Pitanga-Roxa fruits, regarding the content of phenolic compounds and flavonoids and to evaluate their antioxidant capacity, by techniques such as DPPH and FRAP; Evaluate the antimycobacterial activity of the extracts from the broth microdilution technique and obtain the Minimum Inhibitory Concentration (MIC) presented by them; To analyze the cytotoxicity of extracts in normal Vero and HaCat cell lines, using the concentrations obtained as MIC to observe cell viability in the MTT assay and to analyze the production of ROS and Nitric Oxide. As a result, the extracts of wild fruits, Jabuticaba and Pitanga-Roxa, showed higher amounts of polyphenols and better antioxidant capacity than the red fruits, Cranberry and Blueberry. In addition, Jabuticaba and Pitanga-roxa showed better activity in inhibiting MTB, with Minimum Inhibitory Concentration (MIC) of 3.12mg/mL and 6.25mg/mL, respectively, while Cranberry and Blueberry showed MIC of 12.5mg/mL. The antimycobacterial activity showed a positive correlation with the concentration of polyphenols of the extracts. For the evaluation of the cytotoxicity of the extracts, the highest concentrations used were cytotoxic, with the exception of the Jaboticaba extract assay in HaCat cells, in which the desired concentration for the treatment did not present a significant reduction in cell viability. ROS and Nitric Oxide assays reveal that cellular cytotoxicity was not caused by oxidative stress mechanisms, which confirms the antioxidant capacity of the extracts. In conclusion, fruit extracts have a high content of phenolic compounds and are great antioxidants. The cytotoxicity presented occurred at high doses of exposure, generating a limitation to the natural treatment of Tuberculosis, but the beneficial effect in the significant inhibition of mycobacteria was an excellent result achieved, emphasizing the importance of association with other active substances for the development of potential treatments.